Amicus Curiae Institute in the Constitutional Process - KRUSIAN, Anzhelika; ZHYTOTOVSKA, Iryna; MIKHALOV, Volodymyr; IVANCHENKO, Kseniia Kuli; AFANASIEVA, Mariana (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
Given the specifics of constitutional proceedings, the question of the peculiarities of evidence in a constitutional trial is becoming increasingly important. With the adoption of the Law of Ukraine ‘On the Constitutional Court of Ukraine’, for the sake of completeness of the trial, amicus curiae play a significant role in proving – experts and specialists who, by giving opinions on written requests of the judge-rapporteur in the case, reveal the peculiarities of socio-political discussion on complex issues arising in the course of constitutional justice. The purpose of this work is to study the amicus curiae institute, the features of its legal regulation in Ukraine and abroad, as well as to investigate the role of the institute in the constitutional process of Ukraine. The object of the research is the amicus curiae institute in the constitutional process of Ukraine. By examining the amicus curiae institute in the constitutional process of Ukraine, we can conclude that it plays an important role in the completeness of the judicial review of the case. On the one hand, the ‘friend of the court’ is a lobbyist who, thanks to his conclusions, seeks the necessary judicial decision. On the other hand, thanks to the amicus curiae institute, when considering cases that may affect an indeterminate number of persons, civil society (such as NGOs, etc.) can help ensure that the judgment is given in the light of all the circumstances relevant to the cases. However, despite the legislative consolidation of the research institute in the constitutional process of Ukraine, some procedural provisions require further refinement with the use of international experience and advanced scientific works.